Merdeka Belajar dan Belajar dengan Riang Gembira Sejak Dini - EZIK FIRMAN SYAH (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
When teachers apply the concept of independent learning, the teachers do not adapt to the needs of students. Teachers still rely on textbooks as a medium for teaching materials and do not use learning methods and learning media with the needs of students. The purpose of this community service is to socialize the application of independent learning and learning cheerfully from an early age to teachers. The method of community service activities is carried out in the form of webinars using the zoom platform and coordinated together in the form of the International Lecture Share Series activity program. The results of the community service program through this webinar show the data: (1) the suitability of the material with the needs of the participants is 96%, (2) interesting material is responded to by 99%, and (3) the material provides an increase in knowledge and insight by 94%.